2017
DOI: 10.1111/jgh.13627
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease detection and monitoring by measuring biomarkers in non‐invasively collected colorectal mucus

Abstract: Measuring calprotectin and EDN in non-invasively collected colorectal mucus presents a simple and efficient method for IBD detection and monitoring. Excellent performance of EDN for this purpose is reported for the first time. Combining calprotectin and EDN in one test improves IBD detection sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Studies of our group convincingly demonstrated the abundance of inflammatory cells, predominantly neutrophils, in colorectal mucus collected from IBD patients either intrarectally[190,191] or non-invasively[192,193]. Common eosinophil presence in this material was also noted[191,193], especially in UC patients[193], and dramatically increased EDN levels were determined[191,194], typically with higher values in UC compared to CD[194]. Detailed cytological analysis of these samples demonstrated that colorectal mucus from patients with active IBD commonly contains not only huge amounts of neutrophils, but also eosinophils, macrophages, erythrocytes as well as occasional plasma cells, lymphocytes and basophils[193].…”
Section: Eosinophil Impact In the Pathogenesis Of Major Colorectal DImentioning
confidence: 80%
See 1 more Smart Citation
“…Studies of our group convincingly demonstrated the abundance of inflammatory cells, predominantly neutrophils, in colorectal mucus collected from IBD patients either intrarectally[190,191] or non-invasively[192,193]. Common eosinophil presence in this material was also noted[191,193], especially in UC patients[193], and dramatically increased EDN levels were determined[191,194], typically with higher values in UC compared to CD[194]. Detailed cytological analysis of these samples demonstrated that colorectal mucus from patients with active IBD commonly contains not only huge amounts of neutrophils, but also eosinophils, macrophages, erythrocytes as well as occasional plasma cells, lymphocytes and basophils[193].…”
Section: Eosinophil Impact In the Pathogenesis Of Major Colorectal DImentioning
confidence: 80%
“…On the other hand, it should not be forgotten that transepithelial migration of immune cells is a major factor in mucosal disease resolution, as demonstrated for airway diseases[204,205]. Indeed, the presence of both inflammatory cells and biomarkers associated with them significantly decreased in colorectal mucus samples from successfully treated IBD patients[194]. It is, therefore, probable that gradual distal movement of colorectal mucus[189] creates favourable conditions for eliminating dead or obsolete immune cells from the surface of colonic epithelium if inflammation is successfully resolved.…”
Section: Eosinophil Impact In the Pathogenesis Of Major Colorectal DImentioning
confidence: 99%
“…Studies in patients with different forms of GI eosinophilic inflammation have shown increased numbers of activated eosinophils and increased concentrations of extracellular granule protein, suggesting that these cells may be important players in promoting and mediating inflammation in the intestinal mucosa 29, 30, 31, 32. Therefore, it is important to be able to reliably detect and quantify both intact and degranulated eosinophils in order to better understand their involvement and contribution to disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, colorectal mucus could be further explored as a potential sample source. Previous studies have established that colorectal mucus is a rich source of potential IBD biomarkers, as demonstrated by the quantification of calprotectin and eosinophil-derived neurotoxin in mucus samples from IBD patients [ 110 , 111 ].…”
Section: Proteomics and Lipidomics In Ibd Research—going Forwardmentioning
confidence: 99%